Prevalence and characteristics of drug-drug interactions among hospitalised patients in the Capital Region of Denmark. (October 2021) - Pedersen, Hans Kristian Råket; Sørensen, Anne Mette Skov; Schelde, Astrid Blicher; Nyeland, Martin Erik; Jimenez-Solem, Espen
Abstract : Summary: Previous studies on the prevalence of drug-drug interactions (DDIs) have largely been restricted to specific hospital departments. We identified common drug combinations and potential drug-drug interactions (pDDIs) in an entire hospital population throughout 1 year. Frequently administered drug combinations involved analgesics, cardiovascular medicines and gastrointestinal medicines. The prevalence of pDDIs among newly hospitalised patients was 2.6%. The most common pDDIs were ibuprofen – paracetamol, pantoprazole – paracetamol and morphine – paracetamol. Critical pDDIs were rare and only accounted for 0.4% of pDDIs.